Effectiveness, Limitations, and Future Perspectives of CAR-T Cell Therapy in Solid Tumor Treatment: A Narrative Review - Kowalczuk, Dmytro; Kasianik, Viktoryia; Lazitskaya , Darya; Turlej, Kamil; Sobchynskyi, Mykola; Milasheuskaya, Valeryia; Myrnyi, Andrii; Kiełbaszewska, Iga; Surosz, Natalia; Miraniuk, Katsiaryna (Quality in Sport, 2025)
Introduction: In recent years, immunotherapy has revolutionized therapeutic approaches to cancer treatment. Chimeric Antigen Receptor T-cell (CAR-T) immunotherapy has achieved significant success in the treatment of hematological cancers; however, its effectiveness in solid tumors remains limited. Aim of Study: To analyze and summarize the current knowledge on the effectiveness, limitations, development prospects, and improvements of CAR-T cells in the treatment of solid tumors. Brief Description of the State of Knowledge: Despite promising results in hematologic malignancies, the application of CAR-T in solid tumors faces numerous challenges. Key obstacles include the lack of tumor-specific antigens, ineffective targeting and infiltration of CAR-T cells into tumor sites, the immunosuppressive tumor microenvironment (TME), treatment-related toxicity, and antigen escape. The future directions for CAR-T therapy development in solid tumors are the identification of new antigens, optimization of CAR constructs, modification of the TME, and potential combination therapies. Conclusions: CAR-T therapy represents a promising and personalized approach to cancer treatment, with the potential for durable responses and applications in solid tumors, although further improvements are necessary to overcome existing limitations and enhance the effectiveness and safety of this therapy.